Ondansetron versus metoclopramide in prophylaxis of nausea and vomiting for laparoscopic cholecystectomy: A prospective double-blind randomized study - Trichak Sandhu (2018)
OBJECTIVE: Patients who undergo laparoscopic cholecystectomy may be at risk of experiencing postoperative nausea and vomiting. This prospective, randomized, double-blind study compared the prophylactic use of metoclopramide and ondansetron for the treatment of postoperative nausea and vomiting in patients who underwent elective laparoscopic cholecystectomy. METHODS: Eighty patients were randomized into two groups. Patients received ondansetron 4 mg or metoclopramide 10 mg intravenously in a double-blind manner at the end of anaesthesia. RESULTS: The incidence of nausea was 45% for metoclopramide and 20% for ondansetron in the 24 hours postoperatively; the difference was statistically insignificant (p = 0.05). Postoperative nausea score did not show any significant difference between the two group in the first 2 hours (p = 0.3) and 4 hours (p = 0.12) but was significant between 4 and 24 hours (p = 0.02). The incidence of vomiting was 20% for metoclopramide and 2.5% for ondansetron. This difference was statistically significant (p = 0.02). CONCLUSION: Ondansetron 4 mg given intravenously at the end of surgery is effective for preventing vomiting after laparoscopic cholecystectomy. © 2008 Elsevier. All rights reserved.